Diagnostic and genetic markers associated with pulmonary tuberculosis in HIV-infected individuals - Chemych, Mykola; Yanchuk, Svitlana; Zhuk, Kateryna (Journal of Education, Health and Sport, 2021)
An important aspect of monitoring, further timely and effective treatment of HIV-TB coinfection is timely and correct diagnosis based on comprehensive clinical, laboratory and instrumental studies. Many factors play a role in the development of tuberculosis in HIV-infected people, but the key and quite important elements are the study of genetic markers and biomarkers of inflammation. A number of studies have been carried out on inflammatory markers, but IL-6, INF-γ, MIG, CRP, IL-18 remain relevant and insufficiently studied in coinfection. A comprehensive study of them will be important in the screening of HIV-TB coinfection). Determining the presence of (SNP) rs4331426 located in chromosome 18q11.2 in HIV-infected and AIDS patients will solve the issue of predisposition to the development of tuberculosis in the early stages of HIV infection and contribute to the development of further tactics of patients treatment and management.